Art across frontiers : cross-cultural encounters in America : introduction - Lewthwaite, Stephanie (Cambridge University Press, 2013)
This short introduction provides a brief overview of the collection, by addressing the main historiographical and theoretical concerns that unite the individual contributions and by placing the essays in comparative, inter-American and interdisciplinary perspective. What do comparative analyses tell us about patterns of cross-cultural exchange in the visual arts? More specifically, what do these analyses tell us about the role of ethnic agency and audience, and the complex relationship between artistic practice and the ‘mainstream’, the local and the global?